Pemerolehan Bahasa Anak Usia 4 Tahun dalam Kajian Morfologi - Rama Yunita Pratama; Suhermita Sihombing; Ika Febriana (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Acquisition of children's language is an important thing to pay attention to because language is important in children's daily activities. Various factors can influence the process of language acquisition and development. One of the factors in the field of morphology. This study aims to determine the morphological development of the subject of a 4-year-old child with the initials AKP. The method used is qualitative research with a descriptive approach. Data collection techniques used interview techniques, observation, and note-taking as well as data analysis techniques including the reduction stage, the condensation stage, the presentation stage and drawing conclusions. The results showed that the child's morphological development was good. The subject has been able to create affixed words. which consists of the perfixes me-, ber-, di-, se-, and ke-, examples of sentences that are created [the cat gave birth to two]. Then you can confix pe-an, ke-an, as well as the suffixes -I, -an, -right, for example sentences [can you finish your milk?]. The reduplication that is created consists of the words rainbow, color, and day. Infix for children aged 4 years should be able to do by children. However, the AKP subject has not been able to create it.